2016
DOI: 10.1080/07435800.2016.1242603
|View full text |Cite
|
Sign up to set email alerts
|

Acute hormonal findings after aneurysmal subarachnoid hemorrhage – report from a single center

Abstract: Deviations from normal and huge interindividual differences are common in hormone levels during the acute phase of aSAH. Routine assessment of anterior pituitary function in the acute phase of aSAH is not warranted. During the follow-up in the outpatient clinic, hormone concentrations were not measured, which would have brought a more long-term perspective into our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…These three prospective studies are relatively small, with analysis of cortisol dynamics taking place at only a single time point. In a prospective cohort study of 100 patients after SAH, serial measurements of 09:00-h plasma cortisol for twelve days after haemorrhage demonstrated a rate of ACTH/cortisol deficiency of 14% based on a cut-off of 300 nmol/L (71), whereas a recent prospective study by Takala reported a rate of 11% based on a cut-off of 276 nmol/L on six measurements over fourteen days (72). Importantly, Hannon's data showed that ACTH deficiency is often transient after SAH; therefore, a single estimation of plasma cortisol at one time point may miss the diagnosis.…”
Section: Anterior Pituitarymentioning
confidence: 99%
“…These three prospective studies are relatively small, with analysis of cortisol dynamics taking place at only a single time point. In a prospective cohort study of 100 patients after SAH, serial measurements of 09:00-h plasma cortisol for twelve days after haemorrhage demonstrated a rate of ACTH/cortisol deficiency of 14% based on a cut-off of 300 nmol/L (71), whereas a recent prospective study by Takala reported a rate of 11% based on a cut-off of 276 nmol/L on six measurements over fourteen days (72). Importantly, Hannon's data showed that ACTH deficiency is often transient after SAH; therefore, a single estimation of plasma cortisol at one time point may miss the diagnosis.…”
Section: Anterior Pituitarymentioning
confidence: 99%